(untitled) - FAO (Rome, 1997)
The objectives of the consultation were to assess the sunn pest problem in affected countries and to develop strategies for an effective, durable, economic and environmentally friendly cooperative sunn pest management programme.
Keywords: pest control,plant, protection of